Perancangan Sistem Informasi Peminjaman Kredit Berbasis Website Pada Koperasi Cipta Bina USAHA - Heriyanto Heriyanto; Ika Kurniawati (Universitas Majalengka, 2021)
Abstract Cooperatives are one of the aspects that support the community's economy, especially low and middle economic communities. This existing cooperative needs to be developed so that the cooperative can provide good services to the community. Cipta Bina Usaha Savings and Loans Cooperative is one of the cooperatives that helps support the community's economy by providing storage and lending services at low interest rates. The existing data processing information system is felt to be ineffective and inefficient because the existing system is still stand alone. Therefore, it is necessary to develop a credit lending information system at the Cipta Bina Usaha Cooperative which is based on a client server with the aim of accelerating and simplifying the borrowing process and data processing at the Cipta Bina Usaha Cooperative. In the development of this system, the data processed is master data consisting of member data and administrator data as well as transaction data consisting of data on saving deposits, taking deposits, borrowing and data on loan payments. The result of this research and design is a credit lending information system at the Cipta Bina Usaha Cooperative which is based on a client server where the user consists of three parts, namely the chairman of the cooperative, administration and the cashier section. Based on the tests that have been carried out, the system built can help process data effectively and efficiently, both processing member data, data on savings, loans and loan payments.